Skenario konsekuensi analisis pengangkutan LNG Semarang-Yogyakarta dengan simulasi ALOHA - Didik Supriyadi (Journal of Science and Applicative Technology, 2017)
Liquefied Natural Gas (LNG) is one of the potential alternative fuels to replace conventional fuels. Using LNG as fuel in Indonesia especially Yogyakarta will give many advantages, for instance, reduced greenhouse gas emissions so that eco-city in Yogyakarta can be realized. Although LNG has many advantages, LNG still contains many hazards whether during storage or distribution, the major hazard is radiant heat. This study aims to analyze and simulate hazard scenarios when transporting LNG such as fire pools, fireballs and vapor clouds and establishing exclusion zone by Areal Location of Hazardous Atmospheres (ALOHA) simulation. This study assumes that the diameter of the tank leak is 1 in and 3 in. The simulation results the exclusion zone from pool fire’s heat radiation from 1 in and 3 in leaks are more than 14 m and 39 m. While the safe distance of the fireball is 799 m. While in the distance vapor clouds that have a possibility of fire for the diameter leakage of 1 and 3 in are 21 m and 59 m.